O som do silêncio :a angústia social que encobre o luto : um estudo sobre isolamento e sociabilidade entre enlutados do cemitério Morada da Paz (Natal/RN) - Freire, Milena Carvalho B. (2005)
Nowadays, the act of mourning configures as a circumstance of isolation and social anguish due to the impossibility to express the pain by those who suffer the loss of a dear one. At the same time, the symbolic relations established between society and the cemetery contains interpretations about death, pain and fear which confer to the visits a special and individual feature. In this context, this dissertation tries to analyse the formation of a sociability observed among visitors of the Morada da Paz a private cemetery located in Natal/RN as well as the frequency of the visitors to the necropolis. Therefore, the research was accomplished from the observation of the existent relations among these actors whose meetings have procured links based on the experiences´ exchange about pain and bereavement. In this sense, this study tries to analyse, as its principal point, in which way the Morada da Paz space and the relations established there are being appropriate by the visitors in their mourning process, trying to understand what are the role of these bond in the elaboration of the loss for these people